Neuralink’s brain-computer interfaces: medical innovations and ethical challenges - Lavazza, Andrea; Balconi, Michela; Ienca, Marcello; Minerva, Francesca; Pizzetti, Federico Gustavo; Reichlin, Massimo; Samorè, Francesco; Sironi, Vittorio A.; Sosa Navarro, Marta; Songhorian, Sarah (Frontiers in Human Dynamics, 2025)
Neuralink’s advancements in brain-computer interface (BCI) technology have positioned the company as a leader in this emerging field. The first human implant in 2024, followed by subsequent developments such as the Blindsight implant for vision restoration, marks a significant milestone in neurotechnology. Neuralink’s innovations, including miniaturized devices and robotic implantation techniques, promise transformative applications for individuals with neurological conditions. However, these advancements raise critical clinical, ethical, and regulatory questions. From a clinical perspective, BCIs show potential in addressing severe disabilities, but the long-term effects, safety, and usability of these devices remain uncertain. Ethical concerns focus on informed consent, patient autonomy, and the implications of integrating BCIs into human identity. The bidirectional nature of Neuralink’s devices introduces privacy risks, highlighting the need for stringent oversight to safeguard sensitive neural data. Furthermore, the company’s initial lack of transparency, such as delayed trial registration, has drawn criticism from the scientific community for deviating from established norms of research ethics. Regulatory challenges also emerge as BCIs intersect with frameworks governing data privacy, medical devices, and artificial intelligence. The lack of a cohesive legal framework for neurotechnology underscores the importance of developing comprehensive standards to balance innovation with the protection of fundamental rights. Finally, philosophical questions about human identity and agency arise as BCIs blur the boundaries between mind, body, and technology. As BCI technology advances, it is imperative for the scientific community, policymakers, and society to collaborate in addressing the opportunities and risks posed by this transformative innovation.